Virtual learning and higher education - Preston, David Seth (At the interface/probing the boundaries ;, 2004)
It is clear that the Internet and other global information infrastructures provide a major challenge to Higher Education. Questions such as: the extent to which education should become 'virtual', the actual cost and value of such innovation and to what degree such education suits its stakeholders (e.g. students) are now discussed the world over. These issues formed the focus for a conference held at Mansfield College, Oxford in September 2002 and this book contains the most rounded and challenging papers from that event. The book is divided into three main parts which consist of the following themes within Higher Education: current practical and planned uses for Virtual Learning; the future 'Virtual' vision; and the large questions that remain unanswered behind 'Virtual Education'. The contributors range from the nerdy end of experimenters of futuristic innovative technologies via the practitioner middle of well-known organizers of existing virtual systems to the other extreme of the critical engagement of philosophers. This stimulating and important book is aimed at researchers of topics such as technology-driven Education, Philosophy, Innovation and Cultural Studies. It is also meant to appeal to anyone with interest in the impact that the technological virtual will have upon Higher Education in future.